Wieloznaczność zdań pytajnych - Jonkisz, Adam (Filozofia Nauki, 2019)
The aim of this paper is to account for the ambiguity of interrogative sentences by providing a systematic description of the sources of their diverse interpretations. The discussion uses the concepts and methods of classical logic (with set theory) and draws on the results achieved in Polish semiotics, especially on the accounts of questions inspired by Kazimierz Ajdukiewicz’s theory. The method of analyzing the ambiguity of questions proposed in this paper is based on the distinction between what is questioned (the so-called subject of the question) and what is assumed in it (the so-called condition of the question). This method is used to examine the ambiguity of interrogative sentences of various types, as well as to present a way of disambiguating the quantification of interrogatives.